Charitable Crowdfunding in the Philippines: An Integrative Review of Theories, Processes, and Future Directions - Anina Jiliana Alkuino Manuel; Maria Margarita R. Lavides (Pen of Social Science, 2026)
This paper explores the notion of charitable crowdfunding, which sits at the intersection of digital technology and the Filipino value of bayanihan (community spirit).  While charitable crowdfunding is a 21st century phenomenon, it is embedded in a human value that has long been part of Filipino culture. However, there has been a lack of scholarly research on charitable crowdfunding, especially in the Philippine context—a gap which this paper seeks to address through a literature review. The authors initially provide an orientation on the concept of crowdfunding and its related theories and processes. This was followed by a discussion of trends and challenges in an international context prior to focusing on the state and key factors affecting charitable crowdfunding in the Philippines. The article concludes with the study’s implications for research and policy.